The Dynamic Motor Control Index as a Marker of Age-Related Neuromuscular Impairment - Collimore, Ashley N.; Aiello, Ashlyn J.; Pohlig, Ryan T.; Awad, Louis N. (Frontiers in Aging Neuroscience, 2021)
Biomarkers that can identify age-related decline in walking function have potential to promote healthier aging by triggering timely interventions that can mitigate or reverse impairments. Recent evidence suggests that changes in neuromuscular control precede changes in walking function; however, it is unclear which measures are best suited for identifying age-related changes. In this study, non-negative matrix factorization of electromyography data collected during treadmill walking was used to calculate two measures of the complexity of muscle co-activations during walking for 36 adults: 1) the number of muscle synergies and 2) the dynamic motor control index. Study participants were grouped into young (18-35 years old), young-old (65-74 years old), and old-old (75+ years old) subsets. We found that the dynamic motor control index (χ2(2)=9.41, p=0.009), and not the number of muscle synergies (χ2(2)=5.42, p=0.067), differentiates between age groups (χ2(4)=10.62, p=0.031, Nagelkerke R2=0.297). Moreover, an impairment threshold set at a dynamic motor control index of 90 (i.e., one standard deviation below the young adults) was able to differentiate between age groups (χ2(2)=9.351, p=0.009). The dynamic motor control index identifies age-related differences in neuromuscular complexity not measured by the number of muscle synergies and may have clinical utility as a marker of neuromotor impairment.